Additional file 8 of Activation function 1 of progesterone receptor is required for progesterone antagonism of oestrogen action in the uterus - Shi Hao Lee; Chew Leng Lim; Wei Shen; Samuel Ming Xuan Tan; Amanda Rui En Woo; Yeannie H. Y. Yap; Caitlyn Ang Su Sian; Wilson Wen Bin Goh; Wei-Ping Yu; Li Li; Valerie C. L. Lin (figshare, 2022)
Additional file 8. 31 genes significantly regulated between EBP and EB.
Keywords: Genetics